Lactation-promoting ingredients of Hemerocallis citrina Borani and the corresponding mechanisms - Fang, Jinpeng; Xu, Mengtao; Qiu, ZhengYue; Ye, Tian; Jiang, HongLing; Qin, FengYi; Hu, Yuan; Jiang, Faying; Zhong, JuHua; Zhu, Yishuo; Zhao, Lewei; Liu, Xiubin; et al. (Frontiers in Pharmacology, 2024)
Hemerocallis citrina Borani is a traditional folk food used to promote the lactation of postpartum mothers in China; however, the active ingredients and corresponding mechanisms are still unknown. In this study, the lactogenic effect of alcoholic and aqueous extracts of H. citrina was primarily evaluated, and the aqueous extract (1,000 and 2,000 mg/kg) displayed significant lactation-promoting effects. Three eluates of the aqueous extract (0%, 30%, and 50%HCW) were further evaluated for their lactogenic effect, and 30% and 50% HCW showed significant lactation-promoting activity. Nineteen ingredients, including those with a high content of rutin and isoquercetin, were then identified from 30% and 50%HCW using the ultra-performance liquid chromatography-quadrupole-time-of-flight-mass spectrometry (UPLC-Q-TOF-MS) method. Finally, the lactogenic effect of rutin and isoquercetin was evaluated, and both compounds displayed significant lactation-promoting activity. The mechanisms relative to the lactation-promoting active ingredients for H. citrina extracts and compounds are to stimulate the release of prolactin (PRL) and progesterone (P), as well as to induce the expression of prolactin receptor (PRLR) and improve the morphology of mammary tissue. This study first clarified the lactation-promoting active ingredients of H. citrina and the corresponding mechanisms, which provide a new insight into the new lactation-promoting drug and promote the high-value utilization of H. citrina resources.